Fetal Transplant-Induced Restoration of Spatial Memory in Rats with Lesions of the Nucleus Basalis of Meynert - Santucci, Anthony C. (Hindawi Publishing Corporation, 1991)
Bilateral lesions of the nucleus basalis of Meynert (nbM) in rats produced mnemonic deficits when subjects were tested on tests of spatial memory over a period of 3 to 7.5 months postoperatively. The transplantation of cholinergic- rich, fetal ventral forebrain tissue to either two or four frontoparietal cortical sites normalized performance on the spatial memory tasks. However, which transplant condition yielded recovery depended upon the nature of the task and/or posttransplantation interval. When assessed 8 months following transplant surgery, cortical choline acetyltransferase and acetylcholinesterase activity levels in both transplant groups were comparable to those values found in sham-operated animals. These data indicate that fetal transplants can reverse the mnemonic deficits and restore cortical cholinergic neurochemical activity to near-normal levels in rats with nbM lesions.